STRATEGI PENGEMBANGAN USAHA PERCETAKAN EKA MULIA JATI (EMJ) PRODUCTION - MUHAMMAD YUNUS (Ekonomi & Bisnis, 2017)
At the time of this printing companies both small to large are faced with the challenge of globalization and the MEA, coupled with the conditions of the economic downturn in Indonesia in 2016, this has an impact on the level of business competition business increasingly high, therefore employers can determine the right strategy in developing their business and increase revenue is a company that can achieve its goals more efficiently in the future.Research conducted in the printing business EMJ Productions is a survey research. Survey research is research that takes a sample from a population with a list of questionnaire as the main data collectors in the field. Key informants and respondents were obtained by snowball method, namely the acquisition of the target individual interviews based on information from key informants and respondents before. Thus since the beginning of unspecified number of individuals targeted interviews, but more emphasis on completeness and eligibility information obtained to capture the general trend of the business development strategy of printing EMJ Productions. Study period for 6 months, starting in April-September, 2016